Influence of vesicular trichomes of Atriplex nummularia on photosynthesis, osmotic adjustment, cell wall elasticity and enzymatic activity - Paulino, Martha Katharinne Silva Souza (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2020 Elsevier Masson SAS. All rights reserved.